RETRACTED: miRNA-193a-3p Regulates the AKT2 Pathway to Inhibit the Growth and Promote the Apoptosis of Glioma Cells by Targeting ALKBH5 - Cui, Yong; Wang, Qi; Lin, Jing; Zhang, Lei; Zhang, Chi; Chen, Huairui; Qian, Jun; Luo, Chun (Frontiers in Oncology, 2021)
Emerging evidence indicates that microRNA (miR)-193a-3p is involved in the tumor progression of various cancers. However, the biological functions and precise molecular mechanisms of miR-193a-3p in gliomas have not been well documented. Accordingly, this study focused on the tumor suppressor role and molecular mechanisms of miR-193a-3p in glioma cells. miR-193a-3p expression was determined by qRT-PCR in glioma tissues and cell lines. U251 and U87 glioma cells were transfected with a miR-193a-3p mimic. The effects of miR-193a-3p on cell growth and apoptosis were investigated using MTT, colony-forming, and flow cytometry assays. Overexpression of miR-193a-3p in U87 cells also significantly suppressed tumorigenicity and induced apoptosis in the xenograft mouse model. Luciferase assays were conducted to determine if ALKBH5 is a direct target of miR-193a-3p in glioma cells. Immunoprecipitation was used to explore the interaction between ALKBH5 and RAC-serine/threonine-protein kinase 2 (AKT2) in glioma cells. miR-193a-3p was downregulated in glioma tissues and cell lines. miR-193a-3p treatment suppressed proliferation and promoted apoptosis in both U251 and U87 cells. Bioinformatics analysis and luciferase reporter assay identified a novel miR-193a-3p target, ALKBH5. Notably, the antitumor effect of miR-193a-3p transfection in glioma cells may be due to the miR-193a-3p–induced inhibition of AKT2 expression caused by the suppression of ALKBH5 expression. Furthermore, immunoprecipitation indicated that ALKBH5 physically interacted with AKT2 through an RNA-independent mechanism in glioma cells. miR-193a-3p directly targets ALKBH5 to inhibit the growth and promote the apoptosis of glioma cells by suppressing the AKT2 pathway both in vitro and in vivo, and the physical interaction between ALKBH5 and AKT2 is essential for suppressing cell apoptosis by upregulating miR-193a-3p in glioma cells. Our study revealed that the antitumor effects of miR-193a-3p on glioma cells is due to ALKBH5 mediation of the AKT2-induced intrinsic apoptosis signaling pathway.